The use of theory in research relating to open access: Practitioner perspectives. Issue 1 (18th October 2019) - Wakeling, Simon; Pinfield, Stephen; Bawden, David; Robinson, Lyn
ABSTRACT: The relationship between theory and practice has long been considered problematic for many applied academic disciplines. In this short paper we report preliminary findings from a two‐year research project investigating the ways and the extent that theory and practice have interacted in the development of open‐access (OA) approaches to the publishing and dissemination of research outputs. Based on interviews with practitioners and researchers working on OA related issues, we explore the ways in which theory is (and isn't) of value to practice. We find that while practitioners acknowledge that theory has the potential to improve understanding, bestow credibility on work, and codify existing knowledge about OA, they also perceive it as "mood music" to the practical work of OA, lacking explicit links to action.